Sedimentology and Stratigraphy of Two Mesozoic Successions along the Jerantut-Maran Road, Pahang - Mohd Hailami, Nur Nadhirah (2016)
Two neighboring outcrops, a thick conglomerate and sequence of sandstone-mudstone is well exposed and preserved along the road near Pulau Tawar along the Jerantut-Maran Road, Pahang. These outcrops of possible Mesozoic age are being studied in the field and lab to evaluate and interpret the sedimentology and stratigraphy. The integration of field and laboratory analyses are being used to interpret the depositional environment. Data collected include detailed measured sections and facies descriptions. The clast-supported conglomerate of very well-rounded clast shows vary in clasts’ size with poor sorting. Moreover, normal and inverse gradations are shown by these polymict conglomerates. As going upward, thick gravely sandstone with mudstone are found in outcrop 1 indicate change in flow energy. In outcrop 2, there are thick sandstone beds which the individual beds normally thicker than 50cm. The siltstone laminas are present almost on each of sandstone top layer. Sedimentological features suggest that the conglomerate and sandstone-mudstone sequences were possibly deposited in a relatively deep marine environment. The structures of depositions resemble the low sequence character of Bouma sequence which is Ta, massive sand. The depositional environment was interpreted to be submarine fan system.